Writing History at the Ottoman Court : Editing the Past, Fashioning the Future - Fetvaci, Emine; Çıpa, H. Erdem, 1971- (Book collections on Project MUSE., 2013)
Ottoman historical writing of the 15th and 16th centuries played a significant role in fashioning Ottoman identity and institutionalizing the dynastic state structure during this period of rapid imperial expansion. This volume shows how the writing of history achieved these effects by examining the implicit messages conveyed by the texts and illustrations of key manuscripts. It answers such questions as how the Ottomans understood themselves within their court and in relation to non-Ottoman others, how they visualized the ideal ruler, and how they defined their culture and their place in the world.